THE CLASSROOM SOCIAL ENVIRONMENT ROLES AND TEACHER’S ATTITUDE TOWARD WRITING SKILLS IN THE TEACHING AND LEARNING OF THE MALAY LANGUAGE - Nur Nisa Adillah Jafri; Zakiah Noordin; Mohamad Nizam Nazarudin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This research aimed to examine the associations among classroom social environment roles, teachers’ attitudes toward Malay writing skills in teaching and learning, and the potential influence of age and teaching experience. Employing a survey approach, data collection was facilitated through an online questionnaire via Google Forms. The study encompassed a sample of 140 Malay language teachers from the Bangi Zone National School. Data analysis was conducted using Statistical Package for the Social Science (SPSS) version 27.0, encompassing both descriptive statistics (mean, standard deviation, percentage) and inferential statistics (one-way ANOVA test and Pearson Correlation). The findings of this study indicate a notably high level of classroom social environment roles and teacher attitudes. Significant differences were observed in the classroom social environment concerning age, yet no significant variations emerged in teacher attitudes based on age, classroom social environment roles, or teaching experience. Importantly, a positive and significant relationship was established between classroom social environment roles and teachers’ attitudes toward Malay writing skills in teaching and learning. This research carries implications for Malay language teachers, student teachers, the educational community, and the Malaysian Ministry of Education. It highlights the importance of incorporating elements focused on classroom management and the promotion of a positive classroom atmosphere within professional development programs. Teachers and school leaders are encouraged to strategize and actively maintain conducive social environments to enhance the effectiveness of teaching and learning in Malay writing skills.